Visibility-based Optimal Path and Motion Planning - Wang, Paul Keng-Chieh.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This monograph deals with various visibility-based path and motion planning problems motivated by real-world applications such as exploration and mapping planetary surfaces, environmental surveillance using stationary or mobile robots, and imaging of global air/pollutant circulation. The formulation and solution of these problems call for concepts and methods from many areas of applied mathematics including computational geometry, set-covering, non-smooth optimization, combinatorial optimization and optimal control. Emphasis is placed on the formulation of new problems and methods of approach to these problems. Since geometry and visualization play important roles in the understanding of these problems, intuitive interpretations of the basic concepts are presented before detailed mathematical development. The development of a particular topic begins with simple cases illustrated by specific examples, and then progresses forward to more complex cases. The intended readers of this monograph are primarily students and researchers in engineering, computer science and applied mathematics. An understanding of the mathematical development of the main results requires only basic knowledge of mathematical analysis, control, and optimization theories. Some exercises with various degrees of difficulty are provided at the end of the main chapters. The material presented here may serve as a portion of an introductory course or seminar on visibility-based optimal path and motion planning problems with the objective of stimulating interest and further studies in this relatively new area.
Visibility-Based Optimal Path and Motion Planning -- Mathematical Preliminaries -- Static Optimal Visibility Problems -- Visibility-based Optimal Path Planning -- Visibility-based Optimal Motion Planning -- Multiple Observer Cooperative & Non-Cooperative Optimal Motion Planning.
Keywords: Engineering; Artificial intelligence; Computational intelligence; Control engineering; Robotics; Mechatronics; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).; Control, Robotics, Mechatronics; Electronic books